Design of Power Supply for RGB LED Based Lamp Source - Shetty, Divya; Dave, Smit; Shah, Siddhant (International Journal of Engineering and Technology, 2018)
LED lighting is replacing the conventional lighting system at a very fast pace. RGB LED lighting fixtures offer convenient options of color changes to enhance our environment. The forward characteristics of Red, Green and Blue LED’s indicate the region of control to produce acceptable level of light intensities. As the intensity of light produced by an LED is proportional to its forward current, a suitable region is identified to obtain distinctive colors and to explore the energy saving options. The objective of the paper was to provide a suitable control for dimming in the linear region as well as in the nonlinear region of the diode graph. The RGB LEDs have been powered from three push pull converters. Different control methods have been explored and simulated in PSPICE to switch the LEDs as to produce distinctive colors. Every method seems to have its pros and cons. Eventually Voltage mode control is adopted to provide control over the entire region of the diode graph which includes both linear and nonlinear regions which will serve the purpose of dimming. Accordingly, a multi-colored lamp source using RGB LEDs has been designed and the hardware has been developed.